Physical mechanism of swift heavy ion irradiation effect in graphene. Issue 7 (3rd August 2019) - Zhao, Dongdong; Wang, Qiong; Ding, Ji
ABSTRACT: The damage production induced by swift heavy ion irradiation in single-layer graphene (SLG) is investigated by molecular dynamics method. By given energy to a cylindrical region, the latent track consisting of nanopore and non-six-member rings can be produced, which depends on the electronic energy loss (d E /d x ). For SLG, the minimum value needed to generate defects lies in 6.5–10 keV/nm. The latent track formation begins with the decomposition of the structure in energy deposition region until the atomic fragments escape from the surface and gradually decompose into atomic clusters. At the same time, the structure of system also changes. The source power of this phenomena is the accumulation and outward propagation of atomic stress in energy deposition region.